Hubungan Antara Kepribadian Dasar dan Kapasitas Mental dengan Persepsi, Perilaku dan Intensi Integritas Akademik - Hikmah Muktamiroh; Yayi Suryo Prabandari; Soenarto Sastrowijoto (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2015)
Background: Educational institutions must promote the learning of professional behavior as early as possible and conduct evaluation of the implementation, including evaluation of the academic integrity implementation. This study aims to determine the academic integrity perception, behavior and intention of students and their relation to mental capacity and basic personality of students based on the MMPI-2 measurements.Method: This was a non-experimental, conducting quantitative survey involving 209 medical students from one of Faculty of Medicine in Indonesia.Results: The relationship between mental capacity and basic personality based on the measurement of MMPI-2 and the perceptions, attitude and intentions of academic integrity were found. On mental capacity, a correlation was found between potential performance and perceptions (r = 0.169 and p = 0.014) and academic integrity behavior (r = 0.170 and p = 0.014), between adaptability and perception of academic integrity of fellow students (r = 0.149 and p = 0.032), between psychological constraints and academic integrity behavior score (r = 0.137 and p = 0.049) and between moral integrity and perception score of academic integrity (r = - 0.220 and p = 0.001). On the basic personality, there was a correlation between openness to pressure and perceptions of academic integrity of fellow students (r = 0.141 and p = 0.041), as well as between basic personality and perception (r = 0.169 and p = 0.014) and academic integrity behavior (r = 0.154 and p = 0.026).Conclusion: There is a correlation in some variables of mental capacity and basic personality based on MMPI-2 to perception and academic integrity behavior.